Can Forgiving Ever Be a Moral Mistake? Complexifying a Central Commitment of the Christian Moral Life - Pope, Stephen J. (Irish theological quarterly, 2026)
This article proposes that Christian ethics is best understood as offering an affirmative answer to the question, ?Can Forgiving Ever Be a Moral Mistake?? It argues that the most adequate Christian account of forgiveness rests on three claims. First, that we are generally morally obligated to strive to forgive our truly repentant wrongdoers. Second, that in particular circumstances we should strive to forgive our unrepentant wrongdoers when practical wisdom indicates that doing so is best, all things considered. Third, that in other particular circumstances, practical wisdom may indicate that we may, or even should continue to hold justifiable resentment against our wrongdoers and seek to impose just retributive punishment on them. These three claims imply that we would be mistaken to assert either that we must forgive every wrongdoer or that we may only forgive repentant wrongdoers.